Produção de tanase por fermentação submersa através de amostras de penicillium spp isoladas do semi-árido do estado de Pernambuco. - Moura, Cláudia Maria Rocha (2018)
Microbial enzymes are one of the bioactive products have increased their production in recent decades, due to its widespread use in many existing industrial and environmental sectors. There are numerous applications of microbial enzymes in various sectors of biotechnology. Due to its widespread use, several studies have been undertaken to isolate and identify new producers microorganisms, especially those isolated from poorly studied environments and with an immense microbial biodiversity as the northeastern Caatinga. Studies have been conducted with filamentous Penicillium isolated from soil samples of the fungi of Pernambuco Caatinga to produce tannase. Initially enzyme production was performed using selection on solid medium 4 samples. The results showed that the samples called SIS 24 and 25 show the formation of the characteristic halos higher production of enzyme at 37°C, with values of 4.0 and 4.5 cm, respectively. Then molecular and morphological tests for identification of the samples were made which had the largest halos production of tannase and the sample identified as Talaromyces (SIS 24) and Penicillium chrysogenum (SIS 25). The tannase production assays were performed with samples SIS 24 and 25 by submerged fermentation using 4 production media with different compositions at 37 °C, 150 rpm, 168 hours. The results show that the SIS 25 showed the highest enzyme production at 96 hours of production 0.1555 U / mL obtained in the medium 1. Continuing to production studies were performed new production using a 23 full factorial design for alternative media formulation containing organic residues (coffee, grape and orange wastes) under the same conditions used in the previous test. The results showed that the assay 3, which showed a pH 4.8, containing coffee 5g, 12g of grape and orange 5g, presented a lipase activity of 0.210 U / mL. The use of agro-industrial waste emerges as a viable alternative for the development of biotechnology products bioactive media of production.